Liquid-type non-thermal atmospheric plasma ameliorates vocal fold scarring by modulating vocal fold fibroblast. Issue 10 (July 2019) - Won, Ho-Ryun; Song, Eun Hye; Won, Jong Eun; Lee, Hye Young; Kang, Sung Un; Shin, Yoo Seob; Kim, Chul-Ho
Injection laryngoplasty is a widely used therapeutic option for drug delivery into vocal folds (VFs). Efficient injectable materials are urgently needed for treating intractable VF disease. Liquid-type non-thermal atmospheric plasma (LTP) has been found to be useful for various biological applications, including in regenerative medicine. We evaluated the effects of LTP on VF regeneration. Migration and matrix metalloproteinase-2 expression of lipopolysaccharide (LPS)-treated human vocal fold-derived mesenchymal stem cells (VF-MSCs) were enhanced by LTP treatment. LTP treatment not only ameliorated nuclear factor-κB and interleukin-6 activation, induced by LPS treatment, but also the increased manifestation of α-smooth muscle actin and fibronectin, induced by transforming growth factor-ß. In a rabbit VF scarring animal model, histological analyses showed increased hyaluronic acid deposition and decreased collagen accumulation after LTP injection. Videokymographic analysis showed more improved vibrations in LTP-treated VF mucosa compared to those in non-treated group. In conclusion, LTP treatment enhanced the recruitment and activation of VF-MSCs. Regulated extracellular matrix (ECM) synthesis and eventual functional improvement of scarred VFs were observed upon LTP treatment. The results of this study suggest that LTP injection can enhance wound healing and improve functional remodeling following VF injury. Impact statement: Voice disorder has a significant impact on life quality, and one of the major causes of this voice disorder is vocal fold scarring. Therefore, various approaches have been tried to treat for voice disorder. However, no method has satisfied all requirements until now. Plasma medicine, which involves the medical application of plasma, is a rapidly developing field. We have confirmed that liquid-type plasma improved vocal fold scarring by mobilizing and activating vocal fold fibroblast. In conclusion, liquid-type plasma is a potential therapeutic agent for promoting vocal fold scarring through simple injection and it may be an alternative therapeutic agent for the current situation to treat voice disorder.